2003
DOI: 10.1016/s0014-5793(03)00068-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key regions within the Escherichia coli TatAB subunits

Abstract: The twin-arginine translocation (Tat) system catalyzes the transport of folded proteins across the bacterial plasma membrane or the chloroplast thylakoid membrane. In Escherichia coli and most other species, three important tat genes have been identi¢ed but the structure and mechanism of this system are poorly understood; the role and location of TatA are particularly unclear. In this report we have used site-speci¢c mutagenesis to probe the signi¢cance of conserved features of the related TatA/B subunits. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 33 publications
7
44
0
Order By: Relevance
“…Strikingly, replacement of the highly conserved glutamate residue at position 8 with cysteine did not affect the measured Tat transport activity. This observation is consistent with previous reports that substitution of this residue in the E. coli protein with alanine was also well tolerated (48,49). The lowest periplasmic TMAO reductase activity was seen with the substitution of the isoleucine at residue 4.…”
Section: Tatb Is Not Exposed At the Periplasmic Side Of The Cellsupporting
confidence: 92%
See 1 more Smart Citation
“…Strikingly, replacement of the highly conserved glutamate residue at position 8 with cysteine did not affect the measured Tat transport activity. This observation is consistent with previous reports that substitution of this residue in the E. coli protein with alanine was also well tolerated (48,49). The lowest periplasmic TMAO reductase activity was seen with the substitution of the isoleucine at residue 4.…”
Section: Tatb Is Not Exposed At the Periplasmic Side Of The Cellsupporting
confidence: 92%
“…Glu-8 is highly conserved in TatB sequences (5,57) and has been suggested to have a role in linking proton movements to the transport process (5,8). Surprisingly, substitution of Glu-8 in the E. coli TatB protein by either cysteine (this work), alanine (48,49), or glutamine (49) did not affect Tat transport activity, although a Glu to Gln substitution in the chloroplast TatB homolog affected association of the protein with TatC (58). These data suggest that Glu-8 may have a structural rather than mechanistic function in Tat transport as indicated by our modeling studies.…”
Section: Cross-linking Analysis Of Tatb Proteins Carrying Double Cystmentioning
confidence: 84%
“…We observed that mutation in the hinge region affected the C terminus-out topology of TatA. Interestingly, it has been reported that the hinge region and the hydrophobicity of the amphipathic helix are crucial for the Tat function (17,18).…”
Section: Discussionmentioning
confidence: 74%
“…This finding suggests that the lysine 23 is essential for the membrane span topology of the TatA amphipathic helix. Interestingly, it has been recently reported that changing residues in the hinge region of TatA leads to the defect in TMAO reductase export (17,18).…”
Section: Detection Of Cellular Location Of the Tata C Terminus By Usimentioning
confidence: 99%
See 1 more Smart Citation